PENGARUH SOLVABILITAS TERHADAP DIVIDEN MELALUI PROFITABILITAS PADA PERUSAHAAN LQ45 TAHUN 2011 - 2013 DI BURSA EFEK INDONESIA - Dewi Marina (Jurnal Manajerial, 2017)
Dividends are payments made by the company to the shareholders who depend on dividend policy of each company. This study aimed to test the influence of the solvency of the dividend on the company's profitability LQ45 through 2011-2013 in the Indonesia Stock Exchange. This study used a sample of 60 financial statements and tested using the t test and path analysis. Results of testing by t-test showed that the solvency of a direct effect on profitability, solvency does not directly influence the dividend, and directly influence the profitability of the dividend. The results of path analysis on line 1 (p1) that the solvency of the profitability of -0.430 indicates that every increase solvency will cause a decline in profitability, in line 2 (p2) that the solvency of the dividend amounting to -0.062 indicates that every increase solvency will lead to a decrease in the dividend, the lane 3 (p3) is profitability against a dividend of 0.181 indicates that every increase profitability will lead to a dividend increase and in line 4 (p4) that the solvency of the dividend through the profitability of -0.14 indicates that the indirect effect of the dividend solvency through profitability will lead to dividend reduction.